Relation between non-dietary cardiovascular health and costs associated with stroke in the US - Abraham M. Enyeji; Chioma Obi; Armarion Stegall; Jordan Davis; Roha Surani; Jayson Forbes; David L. Wetzell (Journal of Health, Population and Nutrition)
Abstract Background Stroke poses a significant challenge in terms of mortality and healthcare expenditure in the United States, yet the role of Cardiovascular Health (CVH) metrics in alleviating these costs post-stroke remains insufficiently studied. This research aims to evaluate the effectiveness of CVH as a potential tool for secondary prevention by reducing overall healthcare expenditures associated with stroke. Methods A comprehensive cross-sectional analysis was conducted utilizing data from the Medical Expenditure Panel Survey (MEPS) collected between 2011 and 2022. The analytic sample consisted of 85,735 U.S. adults aged 45 years and older, including 896 individuals with a self-reported history of stroke in the unweighted sample. Cardiovascular Health (CVH) score, a composite measure based on the American Heart Association’s Life’s Simple 7 metrics, was used to assess health status. Annual costs were assessed using a generalized linear model with a log link and gamma distribution, followed by a two-part model to account for the presence of both positive and zero costs across disaggregated healthcare categories. The analysis controlled for sociodemographic factors, comorbidity burden, and other relevant covariates, enabling the inclusion of interaction terms to evaluate the impact of variations in CVH on costs between the two populations. Results The analysis indicated that stroke patients faced average annual healthcare expenditures of approximately $76,000, substantially influenced by comorbidity levels as measured by the Grouped Charlson Comorbidity Index (GCCI). Additionally, a one-unit improvement in CVH scores was linked to an estimated reduction of $10,100 ([95% CI, $8,400 – $11,800; p < 0.05]) in healthcare costs. Moreover, the effect of CVH improvements for stroke survivors was comparable to that observed in the non-stroke population. Conclusions The financial strain of stroke on overall healthcare expenditures highlights the critical need for effective secondary prevention strategies. ​Focused efforts on enhancing CVH metrics, especially in managing hypertension and diabetes, show promise in reducing medical costs linked to stroke.​ A heightened emphasis on these health determinants can facilitate optimized resource allocation and better health outcomes for stroke survivors.